ANALISIS STRATEGI BERSAING ASURANSI KENDARAAN BERMOTOR PADA PT ASURANSI ASTRA BUANA - , Hardani Eko Saputro ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research (thesis) is aimed to identify strategies of PT Asuransi Astra Buana by looking at the internal and external environment company. This research also to find out how the competition among the Insurance Industry Indonesia, particularly the General Insurance Industry and how PT Asuransi Astra Buana react to the competition among the general insurance industry. The data used in this research is performance data such as company financial statements for the financial year 2008-2009, the car sales data, data of product profile and products data that offered with price list for each product. The data are taken from annual reports of PT Asuransi Astra Buana, Capital Market Supervisory Agency and Financial Institution (Bapepam-LK), Gaikindo and a competitor company's Annual Report. From the analysis shows with the improved outlook for the insurance business in 2011 mainly for the Class of Motor Vehicle Insurance Business, will lead to intense competition in which insurance companies scramble into the motor insurance business to increase their gross premium written that are directly will result in the emergence of price competition is not healthy. But with the determination of PMK No.74/2007 is the key to handling the war at the same time encourage the growth of the insurance industry in general. From the analysis of generic strategies, Asuransi Astra implement strategies focused on product innovation and service in order to face stiff competition with Product Positioning as a premium brand that describes high quality, exclusive and expensive. The application of this focused strategy based on the premise that Asuransi Astra will be able to serve its strategic targets that have been selected more effectively and efficiently than competitors that compete more broadly.